Complete Molecular and Immunoprotective Characterization of Babesia microti Enolase - Liu, Xiangye; Zheng, Chen; Gao, Xiaoge; Chen, Jiaxu; Zheng, Kuiyang (Frontiers in Microbiology, 2017)
The apicomplexan Babesia microti is the primary causative agent of human babesiosis, one of the most broadly distributed tick-borne diseases worldwide. B. microti undergoes a complex lifecycle within both the mammalian host and the tick vector, and employs several different specific molecular mechanisms to enter host cells. Enolase, the key glycolytic enzyme in intracellular glucose metabolism, can also be expressed on the parasite’s outer surface, binds to human plasminogen, and coordinates apicomplexan parasite invasion of host cells, however it lacks sorting sequences or lipoprotein anchor sites. In the present study, we isolated the coding gene of B. microti enolase (BmEno), expressed it within E. coli and purified the recombinant BmEno protein (rBmEno). Consequently, we confirmed cytoplasmic and surface localization of BmEno via immunofluorescence, and demonstrated that rBmEno catalyzes the dehydration of 2-phospho-D-glycerate to phosphoenolpyruvate. Moreover, our results showed that rBmEno binds to human plasminogen, and that the lysine analog ε-aminocaproic acid significantly inhibited this binding. Furthermore plasminogen bound to rBmEno converts to active plasmin. Additionally, actively immunizing mice with rBmEno could evoke a partial protective immunity against B. microti infection following challenge. In conclusion, B. microti enolase is a multifunctional cytoplasmic protein which is also expressed at the parasitic outer surface, facilitates binding to host plasminogen, and could partially protect hosts against parasite infection.